I@m pro4u2 - Md Azani, Nur Hafzhan; Mohd Rizal, Nur Fitrah; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2019)
Pro4u2 is an online platform for knowledge-sharing of information literacy among students. In Malaysia, information literacy is no longer the norm and the need for only university students. It is even more important for school students at all levels primary and secondary who are sharing the same needs. In schools, they are involved direct and indirectly in information seeking activities to carry out school assignments. This platform is a great alternative for them to find out useful, meaningful, delightful, fruitful and easy-to-understand guides and tips.